ANALISIS TRANSMISI SOLITON PADA SERAT OPTIK DENGAN MENGGUNAKAN METODE KOMPENSASI DISPERSI PERIODIK - Arunglabi (NIM : 23299511), Rismawaty
Abstract : Pulse propagation in optical fiber is influenced by dispersion.. The dispersion make pulses overlap and make a reduction at transmission bandwidth. To overcome this problem the pulse should be compensated in order to be received well in the receiver. One of the solution to repair the pulse-shape from dispersi by setting a compensation fiber (Dispersion Compensation Fiber) at a distance along the existing fiber. The compensation method used in this thesis is the method at Periodic Dispersion Compensation that we can examine how the soliton propagation is influenced by dispersion. Compensation is carried out by calculating the length at the existing fiber, amplifier separation, and the length of compensation fibre need to be set to overcome the dispersion.